Economic evaluation of expanded hemodialysis with the Theranova 400 dialyzer: A post hoc evaluation of a randomized clinical trial in the United States. Issue 3 (19th April 2022) - Blackowicz, Michael J.; Falzon, Luke; Beck, Werner; Tran, Ha; Weiner, Daniel E.
Abstract: Introduction: The Theranova 400 is a medium cut‐off dialyzer that allows for superior clearance of larger middle molecules than traditional high‐flux dialyzers. This study evaluates the association of expanded hemodialysis (HDx) using the Theranova dialyzer versus conventional hemodialysis (HD) with a high‐flux dialyzer on hospitalization rates and healthcare costs as compared to conventional HD in a post hoc analysis of a randomized controlled trial. Methods: In a non‐concealed, 24‐week clinical trial, maintenance HD patients were randomized to receive treatment with either Theranova 400 or a similar size high‐flux dialyzer. Hospitalization rate and average length of stay were calculated from trial data. Use of erythropoiesis‐stimulating agents and iron were assumed to be equal and therefore excluded from the model. Average cost per inpatient day was obtained from a publicly available published source. Probabilistic sensitivity analyses were conducted to account for variability in model inputs. Findings: There were 86 patients (389 patient‐months) in the Theranova group and 85 patients (366 patient‐months) in the high‐flux HD group. All‐cause hospitalization rate was 45% lower with Theranova compared to high‐flux HD (IRR = 0.55; p = 0.05). Average annual estimated cost of hospitalization was 6098 lower with Theranova compared to high‐flux HD. Compared to high‐flux HD, average annual estimated cost associated with Theranova use was 4772 lower per patient. Hospitalization rate and hospital length of stay were the main drivers of cost. Conclusions: Use of the Theranova dialyzer is associated with lower estimated costs of care among maintenance HD patients, driven by fewer hospitalization events.